Determinants of efficacy and safety in epicutaneous allergen immunotherapy: summary of three clinical trials. Issue 6 (13th March 2015) - Senti, G.; von Moos, S.; Tay, F.; Graf, N.; Johansen, P.; Kündig, T. M.
Abstract: The results of our third trial on epicutaneous allergen‐specific immunotherapy (EPIT) will be presented and discussed in the context of our previous trials. This monocentric, placebo‐controlled, double‐blind phase I/IIa trial included 98 patients with grass pollen rhinoconjunctivitis. Prior to the pollen season 2009, patients received six patches (allergen extract: n  = 48; placebo: n  = 50) with weekly intervals, administered onto tape‐stripped skin. Allergen EPIT produced a median symptom improvement of 48% in 2009 and 40% in the treatment‐free follow‐up year 2010 as compared to 10% and 15% improvement after placebo EPIT ( P  = 0.003). After allergen EPIT but not placebo EPIT, conjunctival allergen reactivity was significantly decreased and allergen‐specific IgG4 responses were significantly elevated ( P  < 0.001). In conclusion, our three EPIT trials found that allergen EPIT can ameliorate hay fever symptoms. Overall, treatment efficacy appears to be determined by the allergen dose. Local side‐effects are determined by the duration of patch administration, while risk of systemic allergic side‐effects is related to the degree of stratum corneum disruption.